Why are they not accessing it? User barriers to clinical information access - Elizabeth Laera; Karen Gutzman; Angela Spencer; Charlotte Beyer; Saskia Bolore; John Gallagher; Sean Pidgeon; Ryan Rodriguez (Journal of the Medical Library Association, 2021)
The Medical Library Association’s InSight Initiative provides an open and collaborative environment for library and industry partners to discuss vexing problems and find solutions to better serve their users. The initiative’s fifth summit, continuing work from the previous summit, focused on understanding how users discover and access information in the clinical environment. During the summit, participants were divided into working groups and encouraged to create a tangible product as a result of their discussions. At the end of the summit, participants established a framework for understanding users’ pain points, discussed possible solutions to those points, and received feedback on their work from an End User Advisory Board comprising physicians, clinical researchers, and clinical faculty in biomedicine. In addition to the pain point framework, participants are developing MLA InSight Initiative Learning content with modules to educate librarians and publishers about critical aspects of user behavior. The 2020 Insight Initiative Fall Forum will serve as a virtual home for constructive dialogue between health sciences librarians and publishers on improving discovery and access to information.